Design and Implementation of a High Integrated Noncontact ECG Monitoring Belt (Journal of Fiber Bioengineering and Informatics, 2015)
The ECG plays a key role in the rapid diagnosis of heart diseases such as coronary heart disease, ischemic\rheart disease, myocardial infarction, arrhythmias, etc. Unfortunately, the adhesion of conventional\relectrodes to the skin sometimes is difficult if not impossible due to the wet skin caused by higher\rperspiration. Besides, for the application of long term ECG monitoring, the wet adhesive ECG electrodes\rare easy to cause infection of the wearers' skin. Moreover, in certain situations it is difficult or simply\rtoo time-consuming to undress the patient for an ECG. Therefore, novel ECG monitoring techniques\rare urgently needed. In this paper, an easy-to-use noncontact ECG (NCECG) monitoring node for\rwireless body sensor network was designed and tested. The NCECG node introduced in this paper\ruse the doubled shielded active ECG electrodes, compared with many other two electrodes noncontact\rECG monitoring node, it also added a right-leg-drive circuit to reduce the common mode noise. The\rexperiment result shows that it could accurately monitor the ECG signals while insulated by one layer\rof clothes. Furthermore, the NCECG monitoring node we proposed is high compact and easy to\ruse. Besides ECG monitoring function, it also integrates with temperature, respiration and motion\rstate monitoring function, while the size of the circuit board is just 93 \u00d7 40 mm. And the elastic belt\rarchitecture makes the ECG monitoring much more convenient and easy to use.
Keywords: Active Electrodes; Double Shielded; ECG Monitoring; Wireless Body Sensor Network